Co-inoculation of the endophytes Bacillus thuringiensis CAPE95 and Paenibacillus polymyxa CAPE238 promotes Tropaeolum majus L. growth and enhances its root bacterial diversity - Dal’Rio, Isabella; Lopes, Eliene dos Santos; Santaren, Karen Caroline Ferreira; Rosado, Alexandre Soares; Seldin, Lucy (Frontiers in Microbiology, 2024)
Tropaeolum majus L. is a versatile edible plant that is widely explored due to its medicinal properties, usage in landscaping projects and as a key element in intercropping systems. Its growth could be improved by the use of biofertilizers that can enhance nutrient uptake by the plant or provide tolerance to different abiotic and biotic stresses. In a previous study, 101 endophytes isolated from T. majus roots showed more than three plant growth-promoting (PGP) features in vitro, such as phosphate mineralization and/or solubilization, production of siderophores, antimicrobial substances and indole-related compounds, and presence of the dinitrogenase reductase subunit (nifH) encoding gene. Among these endophytes, two strains -CAPE95 and CAPE238 -had their genomes sequenced in the present study and were identified as Bacillus thuringiensis and Paenibacillus polymyxa, respectively. Metabolic pathways related to the enhancement of nutrient availability (nitrification, nitrogen fixation, sulfate-sulfur assimilation), biosynthesis of phytohormones (ethylene and indole-3-acetic acid precursors) and antimicrobial substances (bacilysin and paenibacillin) were found in their genomes. To evaluate their in vivo PGP capacity in T. majus, greenhouse experiments were conducted with 216 seeds and 60 seedlings, half co-inoculated with the endophytes (treatment) and half inoculated with 1X PBS (control). The treated seeds tended to germinate faster and had a germination index 20.3% higher than the control on the eleventh day of the experiment. Furthermore, the treated seedlings showed significantly higher plant height and leaf diameters (p<0.05). The impact of the endophytes' co-inoculation on the root bacteriome of T. majus seedlings was further analyzed.The bacterial community of the treated plants was significantly different from that of the control plants (p<0.001) and showed a higher richness and diversity of species (Chao and Shannon indexes, p<0.001). A higher relative abundance of potential synergistic plant growth-promoting bacteria was also shown in the bacterial community of the treated plants, such as Lysinibacillus and Geobacter. For the first time, co-inoculation of B. thuringiensis and P. polymyxa was shown to have great potential for application as a biofertilizer to T. majus plants. The bacterial consortium used here could also be explored in other plant species in the future.